Association of PEAR1 rs12041331 polymorphism and pharmacodynamics of ticagrelor in healthy Chinese volunteers - Li, Mupeng; Hu, Yaodong; Wen, Zhipeng; Li, Huilan; Hu, Xiaolei; Zhang, Yanjiao; Zhang, Zanling; Xiao, Jian; Tang, Jie; Chen, Xiaoping (Xenobiotica, 2017)
1. Genetic polymorphisms in platelet endothelial aggregation receptor 1 (PEAR1) were associated with responsiveness to aspirin and P2Y12 receptor antagonists. This study aimed to investigate whether PEAR1 polymorphism is associated with ticagrelor pharmacodynamics in healthy Chinese subjects. 2. The in vitro inhibition of platelet aggregation (IPA) was evaluated before and after ticagrelor incubated with platelet-rich plasma from 196 healthy Chinese male subjects. Eight polymorphisms at PEAR1 locus were genotyped. Eighteen volunteers (six in each rs12041331 genotype group) were randomly selected. After a single oral 180 mg dose of ticagrelor, plasma levels of ticagrelor and the active metabolite AR-C124910XX were measured and pharmacodynamics parameters including IPA and VASP-platelet reactivity index (PRI) were assessed. 3. No significant difference in ticagrelor pharmacokinetics among rs12041331 genotype was observed. As compared with rs12041331 G allele carriers, AA homozygotes exhibited increased IPA after 15 μM ticagrelor incubation (p < 0.01), increased area under the time-effect curve of IPA and lower PRI at 2 h after ticagrelor administration (p < 0.05, respectively). Rs4661012 GG homozygotes showed increased IPA after 50 μM ticagrelor incubation as compared to T allele carriers (p < 0.01). 4. PEAR1 polymorphism may influence ticagrelor pharmacodynamics in healthy Chinese subjects.